Synthesis, Crystal Structures, and DNA Binding Properties of Zinc(II) Complexes with 3-Pyridine Aldoxime. (2nd November 2010) - Konidaris, Konstantis F.; Papi, Rigini; Katsoulakou, Eugenia; Raptopoulou, Catherine P.; Kyriakidis, Dimitrios A.; Manessi-Zoupa, Evy
Abstract : The employment of 3-pyridine aldoxime, (3-py)CHNOH, in Zn II chemistry has afforded two novel compounds: [Zn(acac)2 { (3-py)CHNOH} ]⋅ H 2 O (1 ⋅ H 2 O ) [where acac - is the pentane-2, 4-dionato(-1) ion] and [Zn2 (O2 CMe)4 { (3-py)CHNOH} 2 ] (2 ). Complex 1 ⋅ H 2 O crystallizes in the monoclinic space group P 2 1 / n . The Zn II ion is five-coordinated, surrounded by four oxygen atoms of two acac - moieties and by the pyridyl nitrogen atom of the (3-py)CHNOH ligand. Molecules of 1 interact with the water lattice molecules forming a 2D hydrogen-bonding network. Complex 2 crystallizes in the triclinic P - 1 space group and displays a dinuclear paddle-wheel structure. Each Zn II exhibits a perfect square pyramidal geometry, with four carboxylate oxygen atoms at the basal plane and the pyridyl nitrogen of one monodentate (3-py)CHNOH ligand at the apex. DNA mobility shift assays were performed for the determination of the in vitro effect of both complexes on the integrity and the electrophoretic mobility of pDNA.